Does a fracture of the endocorrector rod affect the quality of life of a patient with spinal deformity? - Mikhail V. Mikhaylovskiy; Elena V. Gubina; Alina A. Alshevskaya (Хирургия позвоночника, 2019)
Objective. To assess the effect of endocorrector rod fractures on the final result of treatment and the quality of life of patients operated on for spinal deformities of different etiology. Material and Methods. The study included 3833 patients older than 10 years who were operated on for spinal deformities of various etiologies and had not been subjected to spinal surgery before admission to the clinic. In the pre- and postoperative periods, spondylograms in frontal and lateral projections in the standing position were studied using the Cobb method, the apical vertebra rotation was determined in accordance with the method of Sullivan et al. Patients answered questions of the SRS-24 questionnaire in the immediate and long-term follow-up periods. Results. In total, fractures of metal implant rods were detected in 85 (2.2 %) patients. The average scoliotic deformity in these patients was 84.5° before surgery, 49.9° after surgery, and 53.7° at the end of the follow-up period (postoperative progression was 3.8°). Thoracic kyphosis was 61.5° before surgery, 44.3° after surgery, and 48.7° at the end of the follow-up period; lumbar lordosis – 68.4°, 54.8°, and 56.5°; and apical vertebra rotation – 55.8°, 33.2° and 35.8°, respectively. According to the questionnaire data, patients estimated their appear- ance after surgery and general appearance somewhat lower and pain as less intense. Indicators of activity and function of the spine after the rod remounting were slightly lower than after the primary surgery. Remounting did not significantly affect the indicator of “consent to surgical treatment under the same conditions” – 80.6 and 80.0 %. Conclusion. Complications in the form of rod fracture do not have a significant negative effect on the treatment result from the standpoint of assessing the quality of life, provided that the corrective effect of the surgical intervention is maintained in the horizontal, frontal and sagittal planes.